Ephemerality and Performance: Sastrugi: Sounds of Antarctic Sea Ice - Chua, Sean Minhui Tashi; Chester, Diana (Leonardo, 2025)
This paper explores the research, making, and performance of Sastrugi: Sounds of Antarctic Sea Ice. Combining the techniques of sonification, field recording, and musique concrète, Sastrugi orchestrates multisensory world building where immersive soundscapes, data-driven violin composition, and expansive visuals narrate the poignant tale of vanishing sea ice in the Antarctic and Southern Ocean. In the face of a record-breaking year for Antarctic sea ice in 2023, this project emerged as a vital testament to the Earth’s changing climate and highlights the power of creative approaches for engaging audiences with science and vast amounts of data.
Keywords: Sørishavet; fotografi; havis; klimaendringer; kunst; musikk; sjøis

Kvalfangst i Sørishavet - Knarvik, Olaf (Kjelda, 2009)
Keywords: Sørishavet; fotografi; hvalfangst

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Mannen med pappnesen (Polarboken, 1986)
Keywords: Antarktis; ekspedisjoner; fotografi; historie